PENINGKATAN HASIL BELAJAR LOMPAT JAUH MELALUI PERMAINAN LOMPAT KANCIL PADA SISWA KELAS IV SDN JAMBANGAN 02 KABUPATEN BATANG TAHUN PELAJARAN 2012 / 2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
Based on observations of the learning process athletics, especially the long jump at the fourth grade students ofSD Negeri Jambangan not going well, because the students' interest in learning the long jump less. From thedescription of the problem, the authors strive to increase learning outcomes through the game long jumpjumping deer that aims to improve learning outcomes in the long jump Elementary School fourth gradestudents through application modification Jambangan 02 deer jumping game. With the formulation of theproblem as follows: